Understanding ‘theory of change’ in international development: A review of existing knowledge - and Stein, Danielle; Valters, Craig (LSE, 2012)
This is a review by Danielle Stein and Craig Valters of the concepts and debates within ‘Theory of Change’ (ToC) material, resulting from a search and detailed analysis of available donor, agency and expert guidance documents. The review was undertaken as part of a Justice and Security Research Program (JSRP) and The Asia Foundation (TAF) collaborative project, and focuses on the field of international development.